Parenting Patterns in Improving Early Children's Socialization Ability - Zulfikar, Muhammad; Rahmayanty, Dinny; Rodia Simanullang, Adelina; Rizwana Akila, Ozza; Alhamdika, Zidan (International Research-Based Education Journal, 2024)
The purpose of this research is to determine the type of parenting style applied by parents, describe the parenting style of children's social skills and to describe parents' efforts to improve interactive abilities. This research uses qualitative research, with a case study approach. The form of care provided by parents generally uses permissive parenting methods. Parental parenting styles influence teenagers ' social skills and parents have tried well to handle children who experience problems in socializing.